The Behavior, Ecology and Evolution of Cichlid Fishes 2021
DOI: 10.1007/978-94-024-2080-7_16
|View full text |Cite
|
Sign up to set email alerts
|

Cichlids as a Model System for Studying Social Behaviour and Evolution

Abstract: The complex social behaviour of cichlids has fascinated scientists and hobbyists alike for almost 100 years. In this chapter, we review the breadth and complexity of cichlid behaviour, particularly with respect to social interactions. We present the case that cichlids are one of the best model systems for understanding both the mechanisms and evolution of behaviour. This is due to the fact that cichlids can be observed without being greatly disturbed, both in the aquarium and ଏeld and because of the unique opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 224 publications
1
13
0
Order By: Relevance
“…Surveys were conducted at each plot using ad libitum counts of individuals of 20 species (or families where resolution to the level of species was not possible, indicated by ‘spp.’; Table 1): in addition to the ten species above, we included Lamprologus callipterus , Lepidiolamprologus attenuatus , Lepidiolamprologus lemairii , Mastacembelus spp ., Neolamprologus savoryi , Neolamprologus modestus , Ophthalmotilapia ventralis , Perissodus spp ., Telmatochromis vittatus and Xenotilapia spp . These species represent a broad cross‐section of fish life in Lake Tanganyika, including the whole range of trophic types from algae–grazer to piscivore (Muschick et al., 2012), (Ronco et al., 2019) and the whole range of social organisation from solitary to cooperative (Jordan et al., 2021). For many fish in Lake Tanganyika, with the exception of pelagic species and those specialising in living in sandy habitats (Konings, 1998), (Koblmüller et al., 2004), rocks fulfil at least one of the three essential roles in a fish's life cycle: (i) they serve as the substrate on which eggs are deposited (Nagoshi, 1983), (Sefc, 2011); (ii) they provide the surface on which the primary food source grows in the form of algae and associated invertebrates (Kotrschal & Taborsky, 2010), (Ronco et al., 2019); and (iii) they form the shelters in which fish seek refuge from predation throughout their lives, from hatching into adulthood (Balshine et al., 2001), (Heg et al., 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys were conducted at each plot using ad libitum counts of individuals of 20 species (or families where resolution to the level of species was not possible, indicated by ‘spp.’; Table 1): in addition to the ten species above, we included Lamprologus callipterus , Lepidiolamprologus attenuatus , Lepidiolamprologus lemairii , Mastacembelus spp ., Neolamprologus savoryi , Neolamprologus modestus , Ophthalmotilapia ventralis , Perissodus spp ., Telmatochromis vittatus and Xenotilapia spp . These species represent a broad cross‐section of fish life in Lake Tanganyika, including the whole range of trophic types from algae–grazer to piscivore (Muschick et al., 2012), (Ronco et al., 2019) and the whole range of social organisation from solitary to cooperative (Jordan et al., 2021). For many fish in Lake Tanganyika, with the exception of pelagic species and those specialising in living in sandy habitats (Konings, 1998), (Koblmüller et al., 2004), rocks fulfil at least one of the three essential roles in a fish's life cycle: (i) they serve as the substrate on which eggs are deposited (Nagoshi, 1983), (Sefc, 2011); (ii) they provide the surface on which the primary food source grows in the form of algae and associated invertebrates (Kotrschal & Taborsky, 2010), (Ronco et al., 2019); and (iii) they form the shelters in which fish seek refuge from predation throughout their lives, from hatching into adulthood (Balshine et al., 2001), (Heg et al., 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Notable exceptions include translocation experiments that showed that within a species the length for which a defended resource can be expected to be exploited (Field et al., 2010) or the availability of high‐quality defendable resources (Komdeur, 1992) can have drastic effects on the expression of sociality. Importantly for the scope of this manuscript, fish have proven useful in this context, because patterns observed in correlational data can be experimentally probed: the resources defended by social species, namely anemones, corals, rocks and/or shells, can be easily manipulated and behavioural responses documented, a work pioneered by Michael Taborsky ((Tab orsky & Wong, 2017), (Jordan et al., 2021); see also below and Discussion for additional details).…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating sexbiased dispersal in fishes have so far produced examples of both male-biased (e.g., brook trout, Salvelinus fontinalis, [29]; Neolamprologus pulcher, [30]; three-spined sticklebacks, Gasterosteus aculeatus, [31]) and femalebiased dispersal (e.g., Asian Seabass, Lates calcarifer, [32]). The variation that exists across species in terms of whether males or females are the more dispersing sex is particularly well-represented within fish family Cichlidae, which is also well-regarded for its extreme cross-species variation in social traits [33,34]. Here, male-biased dispersal has been detected in rock-and sand-dwelling cichlids of Lake Malawi Pseudotropheus spp.…”
Section: Introductionmentioning
confidence: 91%
“…A large proportion of East African cichlid species are philopatric and stay in or regularly return to a particular area. It is thus feasible to conduct behavioral observations, collect genetic material, tag individuals, and conduct release and recapture experiments to follow wild individuals and populations through time [ 31 ]. If species are not philopatric, field-based cage experiments that can harbor dozens to hundreds of individuals are still possible [ 32 ].…”
Section: Field Collection and Laboratory Culturementioning
confidence: 99%